A Generational Approach to the Crisis Parties: Common Origins and Common Features - Jorge Bronet; Rosa Borge (Acta Politologica)
Over the past two decades, Western Europe has witnessed a boom in new political parties that have obtained significant electoral results, naturally embracing digital technologies and seeking to challenge their traditional counterparts by reconnecting with the citizenry. With a critical review of the main attributes and concepts used so far by the most relevant literature, we propose a new perspective to delimit this phenomenon that allows us to observe it as a whole and not as a particular case. By focusing on scholars who underscore the importance of the historic origin to understand parties, we formulate a generational approach for setting a cohort and analyzing whether the fact that parties share contextual conditions when they emerge also means they have some common features, in contrast to the older political parties. We focus on three dimensions usually highlighted by case studies: strong digitalization (Gerbaudo 2018, 2019), thin structure (Biancalana 2016; Raniolo, Tarditi 2020; Tormey 2015) and more members (van Haute, Ribeiro 2022). In order to do so, we verify it empirically by operationalizing the Political Party Database PPDB round 2 with a sample of 98 parties from 13 Western European countries, comprising 29 new parties (that we generationally call crisis parties) and 69 older parties. This paper aims to better determine whether these new parties, which emerge in a particular political scenario, are (or were) different. The results show that the crisis parties are more digitalized, have less structure and have more members than the previous cohorts parties. In this sense, these crisis parties have brought about some relevant changes in Western European party systems.